The effect of milrinone infusion on right ventricular function during coronary anastomosis and early outcomes in patients undergoing off-pump coronary artery bypass surgery - Jo, Hyong Rae (The Korean Society of Anesthesiologists, 2010)
BACKGROUND: During coronary anastomosis in off-pump coronary artery bypass surgery (OPCAB), hemodynamic alternations can be induced by impaired diastolic function of the right ventricle. This study was designed to examine the effect of milrinone on right ventricular function and early outcomes in patients undergoing OPCAB. METHODS: Forty patients undergoing OPCAB were randomly assigned in a double-blind manner to receive either milrinone (milrinone group, n = 20) or normal saline (control group, n = 20). Hemodynamic variables were measured after pericardiotomy (T1), 5 min after stabilizer application for anastomosis of the left anterior descending coronary artery (LAD, T2), the obtuse marginalis branch (OM, T3), the right coronary artery (RCA, T4), 5 min after sternal closure (T5), and after ICU arrival. The right ventricular ejection fraction (RVEF) and right ventricular volumetric parameters were also measured using the thermodilution technique. For evaluation of early outcomes, the 30-day operative mortality and morbidity risk models were used. RESULTS: There was no significant difference in hemodynamic variables, including mean arterial pressure, between the 2 groups, except for the cardiac index and RVEF. The cardiac index and RVEF were significantly greater at T3 in the milrinone group than in the control group. CONCLUSIONS: Continuous infusion of milrinone demonstrated a beneficial effect on cardiac output and right ventricular function in patients undergoing OPCAB, especially during anastomosis of the graft to the OM artery, and it had no adverse effect on early outcomes.